Obstáculos em torno da feminilidade - Pontes, Lusimar de Melo (2011)
This master thesis aims to investigate the female subject and its issues concerning femininity. In this sense, it discusses the traits that could enhance or contribute to the creation of a network of obstacles or impediments to femininity. The theoretical framework of the dissertation is based on psychoanalysis, especially the work of Sigmund Freud and Jacques Lacan. This study aims to address questions arising from clinical practice, since it was a combination of clinical facts that raised the questions which led to the beginning of this path of study. Therefore, this research has clinical experience as a starting point, being conducted on a clinical case specifically chosen for demonstrating the drama of a young woman faced with the issues involving the loss of virginity and the non-recognition of this experience as a mark of the process of becoming a woman before society. The path taken by the young woman toward womanhood marks the psychic nature of this process and shows that on the issues surrounding femininity the logic of recognition may be in check. Psychoanalysis, through Lacan, states that "Woman does not exist," concluding that in the constitution of female sexuality there is something enigmatic and unique, beyond the Oedipal and castration complexes, making it impossible for a single and universal path to be established in the process of becoming a woman. Becoming man or woman is a matter of sexualization, a matter of choice of jouissance. The consequence of this choice is that masculine and feminine are divided according to the castration mode of jouissance in relation to the Other sex: one phallic and the other not-all. The phallus is the signifier of phallic jouissance, which inscribes the logic of phallic signification. The Other jouissance, the feminine one, has to do with a kind of paradox of recognition, unlike the male position. For there is no significant determining the woman in the unconscious and, therefore, every woman is a construction. Women, without a symbolic feature defining them, are required to construct, and create piece by piece, their own version of femininity. Obstacles to femininity can be accentuated if the woman does not accept that this trait is absent, condemning her to an eternal quest for recognition which would point to hysteria